2013
DOI: 10.1186/1471-2377-13-133
|View full text |Cite
|
Sign up to set email alerts
|

5-year survival and rehospitalization due to stroke recurrence among patients with hemorrhagic or ischemic strokes in Singapore

Abstract: BackgroundStroke is the 4th leading cause of death and 1st leading cause of disability in Singapore. However the information on long-term post stroke outcomes for Singaporean patients was limited. This study aimed to investigate the post stroke outcomes of 5-year survival and rehospitalization due to stroke recurrence for hemorrhagic and ischemic stroke patients in Singapore. The outcomes were stratified by age, ethnic group, gender and stroke types. The causes of death and stroke recurrence were also explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
4
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 26 publications
(20 reference statements)
12
46
4
3
Order By: Relevance
“…In keeping with previous studies, advanced age could lead to severe stroke and have a deleterious impact on its prognosis [12][13][14][15][16][17][18]. Notably, rare studies indicated initial pulse rate as an important mortality predictor for ischemic stroke.…”
Section: Mortality Predictors and Survivalsupporting
confidence: 78%
See 2 more Smart Citations
“…In keeping with previous studies, advanced age could lead to severe stroke and have a deleterious impact on its prognosis [12][13][14][15][16][17][18]. Notably, rare studies indicated initial pulse rate as an important mortality predictor for ischemic stroke.…”
Section: Mortality Predictors and Survivalsupporting
confidence: 78%
“…NIHSS score at admission have been determined as other predictive factors for severe stroke and death of ischemic stroke patients [13][14][15][16][17][18]. Therefore, it is obviously important to recognize the most considerable economic and mortality predictors of stroke.…”
Section: Journal Of Neurology and Neurophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Literatürdeki çalışmalar incelendiğinde, üst basamak merkezlerde yapılmış çalışmalarda bir yıllık mortalite oranlarının %25-30 civarında olduğu görülmektedir (22,23,24). Bu çalışmada ise birinci yıl sonundaki mortalite oranı %45 olarak hesaplanmıştır.…”
Section: Discussionunclassified
“…(1,2) As one in three affected persons remains permanently impaired due to persistent motor deficits, research is necessary to develop more effective treatments that can increase quality of life for these patients. (3) Early rehabilitation is crucial in maximising functional recovery, (4,5) yet the optimal treatment strategy is still not well defined.…”
Section: Introductionmentioning
confidence: 99%